Títulos de Participación en el Patrimonio (TPP) - Baldeón, Francisco (2023)
This article studies the Non-Stock Equity Instrument, an equity financial instrument that grants its holder a specific participation in the results of the issuing company without granting the holder the status of shareholder, which, despite being expressly provided for in Peruvian law and in comparative law, has been forgotten in financial practice.The objective of this study is to understand the competitive advantages of the Non-Stock Equity Instrument for both issuers and holders, which make it a financial instrument to be considered in the capital market.